Luminescent Electrochromic Device Based on a Biohybrid Electrolyte Doped With a Mixture of Potassium Triflate and a Europium beta-diketonate Complex - Fernandes, M.
An amorphous poly(epsilon-caprolactone) (PCL(530))/siloxane hybrid doped with potassium triflate (KCF3SO3) and Eu(btfac)(3)phen (where btfac(-) is 4,4,4-trifluoro-1-phenyl-2,4-butanedionate and phen is 1,10-phenantroline) was synthesized by the sol-gel method. This hybrid exhibits a maximum and constant absolute emission quantum yield value of 0.26 +/- 0.03 under excitation within 330-360 nm. The performance of a prototype ECD based on a glass/ITO/WO3/electrolyte/NiO/ITO/glass incorporating this material is very encouraging. The device exhibited switching time around 50 s, an optical density change of 0.06, and a coloration efficiency of 23 cm(2)C(-1) in the 2nd cycle. This work demonstrates that the combined use of an ionic salt and a lanthanide complex as active species of an ECD's electrolyte offers attractive new prospects for the fabrication of light emitting electrochromic windows.